Host Evasion by Burkholderia cenocepacia - Ganesan, Shyamala; Sajjan, Umadevi S. (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia cenocepacia is an opportunistic respiratory pathogen of individuals with cystic fibrosis (CF). It is one of the highly transmissible species of Burkholderia cepacia complex and very resistant to almost all the antibiotics. Approximately 1/3rd of B. cenocepacia infected CF patients go on to develop fatal ‘cepacia syndrome’. During the last two decades, substantial progress has been made with regards to evasion of host innate defense mechanisms by B. cenocepacia. Almost all strains of B. cenocepacia has capacity to survive and replicate intracellularly in both airway epithelial cells and macrophages, which are primary centennials of the lung and play a pivotal role in clearance of infecting bacteria. Some strains of B. cenocepaica, which express cable pili and the associated 22kDa adhesin are also capable of transmigrating across airway epithelium and persist in mouse models of infection. In this review, we will discuss how this type of interaction between B. cenocepacia and host may lead to persistence of bacteria and contribute to lung inflammation in CF patients.